Optimization of Sports Management for Management of Student Sports Clubs and Activity Units - Taroreh, Bangkit Seandi; Aliriad, Hilmy; Rahmadhanty, Oktaviarini Yahya; Munawar, Sayyid Agil Rifqi; Nugroho, Mahir Dwi; Damayanti, Yuniarti Sani (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Optimal sports management plays an important role in improving the effectiveness of managing sports clubs and student activity units in higher education environments. This study aims to produce a sports management optimization model for managing sports clubs and student activity units. This study uses a qualitative descriptive approach. Data were collected through in-depth interviews, direct observation, and document studies at the karate martial arts sports activity unit. Participants in this study consisted of coaches, supervising lecturer, UKM manager, members (active students aged 18-24 years) in the karate student martial arts activity unit. The analysis was carried out using qualitative analysis methods to identify patterns and main challenges in managing sports student activity units. The results of the study indicate that the main challenges include 1) suboptimal financial support, 2) suboptimal facility support, 3) lack of active student participation in sports student activity unit activities, 4) suboptimal implementation of training programs, 5) suboptimal promotion methods for sports student activity units to new students, 6) need for leadership training, 7) need for the use of sport science technology. Based on the results of the study, the researcher recommends a sports management optimization model for managing sports clubs and student activity units